Standard Dose Development for Medications Commonly Used in the Neonatal Intensive Care Unit - Robinson, Christine A (Pediatric Pharmacy Advocacy Group, 2014)
OBJECTIVES: To establish standardized, rounded doses of medications for neonates in the neonatal intensive care unit (NICU) through a multi-institutional peer-reviewed process. METHODS: Pediatric faculty and pediatric pharmacy residents from the Ernest Mario School of Pharmacy (Piscataway, NJ) conducted a systematic review of rounded, weight-based medication information for neonatal patients from September 2010 to April 2011. After initial review, an expanded workgroup of expert neonatal pharmacy clinicians from academic institutions throughout the United States were invited to conduct a final review. The workgroup identified 74 medications or indications in the NICU. Recommended standardized doses were established for discrete weight categories at workgroup consensus web meetings conducted from June to December 2011. Workgroup recommendations were cross-referenced with published neonatal pharmacology resources. Consensus was obtained when references provided insufficient information on medication information. RESULTS: Seventeen weight categories of increasing ranges were used, from 40 g for the lowest weights (e.g., 410–450 g) to 840 g for the highest weights (e.g., 3660–4500 g). Medications were divided into 3 categories of administration routes: oral (n = 4), intermittent intravenous (n = 64), and other (e.g., intramuscular; n=6). A significant majority of standardized doses (84%) were within 15% of their corresponding weight-calculated dose. CONCLUSIONS: Establishment of a portfolio of standardized, rounded doses of medications commonly used in the NICU was feasibly established by a multi-institutional peer review process, with the great majority of standardized doses being within clinically acceptable ranges of administration. Use of standardized, rounded doses for reduction in dosing errors may be feasible on a systematic level.